Rekonstruksi Konsep Pendidikan dalam Al-Qur'an dan Relevansinya terhadap Perkembangan Peradaban Islam - Wira Elmuhriani; Anita Pronika (Medan Resource Center, 2026)
Qur'anic education constitutes the fundamental framework for developing individuals who possess faith, knowledge, moral integrity, and the capacity to advance Islamic civilization. Contemporary Islamic education, however, faces persistent challenges, including the dichotomy between religious and secular sciences, moral degradation, and the weak integration of Qur'anic values with modern scientific development. This study aims to analyze the educational concepts presented in the Qur'an, reconstruct these concepts through the maudhu'i (thematic) interpretation approach, and examine their relevance to the development of Islamic civilization. The research employed a qualitative library research design using the Qur'an and classical as well as contemporary tafsir as primary sources, complemented by scholarly books and journal articles as secondary sources. Data were analyzed through the maudhu'i tafsir method by identifying, classifying, interpreting, and synthesizing educational verses, followed by historical analysis. The findings indicate that Qur'anic education represents a holistic and integrative educational system that harmoniously develops intellectual, spiritual, moral, and social dimensions. The reconstructed framework emphasizes five principal orientations: nurturing servitude to Allah, cultivating humanity's role as khalifah, advancing knowledge as a divine trust, fostering noble character, and building a civilized society through the integration of faith, knowledge, and righteous action. These principles remain highly relevant for strengthening Islamic civilization in the contemporary era.